Identification of circulating small non-coding RNAs in relation to male subfertility and reproductive hormones. (15th July 2019) - Kumar, Kishlay; Trzybulska, Dorota; Tsatsanis, Christos; Giwercman, Aleksander; Almstrup, Kristian
Abstract: Male subfertility is often associated with sub-optimal health status and traditional semen and hormone analysis reveal only limited information about the reduced fertility potential. Circulating small non-coding RNAs (sncRNAs) are paracrine and endocrine messengers, with prognostic potential. Here, we utilised small RNA-Seq to identify novel cell-free circulating sncRNAs that could act as potential biomarkers of male subfertility. We analysed sera from twelve subfertile men and four controls. The subfertile men were further sub-divided into the three groups based on reproductive hormone levels: group 1 (n = 4): hormone levels similar to the controls, group 2 (n = 4) showing elevated FSH levels, and group 3 (n = 4) with low total testosterone (TT). Total RNA was extracted from serum and sequenced to identify miRNAs and piRNAs. Selected sncRNAs were qPCR validated in a larger and independent cohort of subfertile men (n = 57) and normozoospermic controls (n = 19). RNA-Seq resulted in the identification of 1123 and 330 circulating miRNAs and piRNAs, respectively. Several miRNAs and piRNAs were differentially (p = 0.05) present between controls and subfertile men. Subfertile men with low TT appeared to have a distinct sncRNA profile, compared to group 1 and 2. Validation of two miRNAs (hsa-miR-542-5p and hsa-let-7i-3p) and one piRNA (hsa-piR-26399) in an independent cohort confirmed a significant difference in circulating levels between subfertile and control men. Enrichment analysis of the putative miRNA targets showed association with steroid biosynthesis pathway highlighting a potential regulatory role of these miRNAs. We propose that circulating sncRNAs may represent new important functional biomarkers in male reproductive endocrinology.